2019
DOI: 10.1177/0021998319857807
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite coatings on steel for enhancing the corrosion resistance: A review

Abstract: Steel is known for its low cost of fabrication, high mechanical strength and hence is extensively used for drilling equipment, pipelines, ship building and offshore structures. Corrosion of steel is a costly problem in many applications especially in oilfield and marine environments which are known for the high temperature, high pressure and corrosive conditions. In this paper, nanocomposite coating is being explored as the preferred strategy to improve corrosion resistance for steel. Here, we will give detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(32 citation statements)
references
References 114 publications
1
31
0
Order By: Relevance
“…The results confirm that hybrid nanofillers matrix provides an extra barrier layer and lengthens the diffusion path of corrosive agents at the coating/metal interface to prevent electrolyte penetration on the coated metal surface 14,59 . Enhancement in anticorrosion performance can be ascribed to their two‐dimensional sheet structure, uniform dispersion and absence of exposed tiny pores and exfoliation of GO‐nanoclays hybrid within the epoxy matrix 60,61 . This is in agreement with the study by Xu et al 12 They found that coating containing 0.5 wt% HNTs and 0.8 wt% graphene oxide (H05G08EP) endowed an excellent corrosion resistance and endured the longest neutral salt spray time.…”
Section: Resultssupporting
confidence: 90%
“…The results confirm that hybrid nanofillers matrix provides an extra barrier layer and lengthens the diffusion path of corrosive agents at the coating/metal interface to prevent electrolyte penetration on the coated metal surface 14,59 . Enhancement in anticorrosion performance can be ascribed to their two‐dimensional sheet structure, uniform dispersion and absence of exposed tiny pores and exfoliation of GO‐nanoclays hybrid within the epoxy matrix 60,61 . This is in agreement with the study by Xu et al 12 They found that coating containing 0.5 wt% HNTs and 0.8 wt% graphene oxide (H05G08EP) endowed an excellent corrosion resistance and endured the longest neutral salt spray time.…”
Section: Resultssupporting
confidence: 90%
“…Since metal corrosion has detrimental effects on the economies of nations, opposing arguments have been recognized to boost the corrosion resistance of metallic components. Polymer coatings and epoxy resin are represented as the most common material used to distinguish metallic surfaces from corrosive conditions as protective coatings [190,191]. While epoxy coatings are regarded as thinking leads to the provision of an effective, convenient and economical process, but it suffers from certain drawbacks, such as corrosive agent permeability, hydrolytic degradation, and can therefore not provide long-term protection against corrosion [192].…”
Section: Corrosion Protection 441 Corrosion Protection By Functionmentioning
confidence: 99%
“…Recent research has shown that adding nanoparticles (NP) such as SiO 2 , TiO 2 , ZnO, Al 2 O 3 , MWCNT, and CaCO 3 in coatings results in improving the thermal stability of the polymer and enhancing scratch and abrasion resistance [119]. As an example, incorporating MWCNT in polymer matrices improves the wear resistance and reduces the friction of the composite when upgraded [120].…”
Section: Chemical Properties Of Nanofiller-tpu Nanocompositesmentioning
confidence: 99%